Bidirectional Associations Between Adiposity and Cognitive Function: A Prospective Analysis of the Canadian Longitudinal Study on Aging (CLSA). Issue 2 (29th May 2022) - Nazmus Sakib, Mohammad; Best, John R; Ramezan, Reza; Thompson, Mary E; Hall, Peter A
Abstract: Background: Theoretical perspectives suggest that adiposity and cognitive function may be bidirectionally associated, but this has not been examined in a large-scale data set. The current investigation aims to fill this gap using a large, representative sample of middle-aged and older adults. Methods: Using data from the Canadian Longitudinal Study on Aging ( N = 25 854), the bidirectional hypothesis was examined with 3 indicators of cognitive function (ie, executive function, processing speed, and verbal fluency) and adiposity (ie, waist circumference [WC], body mass index [BMI], and total fat mass). We used multivariate multivariable regression and structural equation modeling to assess the prospective associations between adiposity and cognitive indicators. Results: Analyses revealed that higher baseline WC was associated with higher Stroop interference at follow-up for both middle-aged (standardized estimate, β = 0.08, 95% confidence interval [CI] 0.06, 0.10) and older adults (β = 0.07, 95% CI 0.04, 0.09). Similarly, higher baseline Stroop interference was also associated with higher follow-up WC in middle-aged (β = 0.08, 95% CI 0.06, 0.10) and older adults (β = 0.03, 95% CI 0.01, 0.06). Effects involving semantic fluency and processing speed were less consistent. The earlier effects were similar to those observed using other adiposity indicators (eg, BMI and total fat mass) and were robust to adjustment for demographics and other cofounders, and when using latent variable modeling of the adiposity variable. Conclusion: Evidence for a bidirectional relationship between adiposity and cognitive function exists, though the associations are most reliable for executive function and primarily evident at midlife.